Implementasi Kurikulum Darurat di Masa Pandemi COVID-19 Dalam Upaya Pemenuhan Hak Pendidikan - Jaka Bangkit Sanjaya; Rastini Rastini (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The WHO-19 pandemic is a state emergency that has major consequences for all countries, including Indonesia. These consequences occur in various fields of life, including education. Many Indonesian citizens feel that their education rights are not fulfilled because they have to undergo distance education. This makes the government have an important role to play in overcoming this problem, namely by issuing an emergency education curriculum. The curriculum is a curriculum that is in common with the National Curriculum because it is a simplification. This curriculum also, when viewed from the perspective of Constitutional Law, is a great hope so that the education rights of Indonesian citizens can be fulfilled. This hope can be created because the learning prioritizes the achievement of student understanding. So that with the Emergency Curriculum, it can be a step to adapt and proceed towards normal state conditions, especially to fulfill the education rights of Indonesian citizens. In writing and describing the analysis, the author uses the juridical normative research method.